A language for modeling the morphogenesis process of biological system using MAS - Angelini, José O. (2015)
The biological systems are Complex Adaptive Systems that can build a complex structure using interaction between cell and its environment. The process is called morphogenesis, it is study by developmental biology and applied by tissue engineering and regenerative medicine. Computational models are used by researchers to organize and communicate ideas, test hypotheses and abstractly represent behaviors, etc. Although, Agent Based Models are used in biological systems, it is necessary appropriate domain-oriented language. This work shows the progress made in the definition of a language for modeling and simulation of such systems, in order to hide details of implementation and execution of a simulation. The language concepts are demonstrated using, as study case, the morphogenesis of a heart valve in vitro.